1996
DOI: 10.1111/j.1365-2125.1996.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential greater than additive vasorelaxant actions of milrinone and nitroglycerin on human conduit arteries

Abstract: 1 The mechanism of vasorelaxation for phosphodiesterase I11 inhibitors is mediated by increase of cAMP whereas for nitrovasodilators, cGMP. Pretreatment with the combination depressed contraction to a higher extend compared with milrinone alone (P < 0.05) for the K+-induced contraction and to NTG alone ( P < 0.05) in U46619-induced contraction. Treatment with the combination also shifted ECS0 rightward and this shift was significantly more than that caused by treatment with NTG alone (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In patients with pulmonary hypertension associated with congestive heart failure, a single intravenous bolus of milrinone decreased both PAP and pulmonary vascular resistance [17]. He et al [18] reported that in human conduit arteries precontracted with either U46619 or potassium the combined treatment with milrinone and nitroglycerin resulted in greater relaxation than that with milrinone alone [18]. In our study, the addition of milrinone did not further vasodilate lungs obtained from LPS-treated rats ventilated with NO (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…In patients with pulmonary hypertension associated with congestive heart failure, a single intravenous bolus of milrinone decreased both PAP and pulmonary vascular resistance [17]. He et al [18] reported that in human conduit arteries precontracted with either U46619 or potassium the combined treatment with milrinone and nitroglycerin resulted in greater relaxation than that with milrinone alone [18]. In our study, the addition of milrinone did not further vasodilate lungs obtained from LPS-treated rats ventilated with NO (Fig.…”
Section: Discussionsupporting
confidence: 47%
“…This, as well as the increased CO in the milrinone group, is presumed to be the result of the uncompensated vasodilatory effect of milrinone. Preload reduction would also be complicated with administration of nitrate agents with additive vasorelaxation effect (16). Given normal or near-normal RV afterload, preload is the determinant for the RV performance (17).…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are useful in postoperative management of patients who undergo open heart surgery, particularly in patients who present ventricular dysfunction and receive arterial grafts for coronary artery bypass surgery. Favorable effects of inamrinone on the IMA [76,[86][87][88] have been reported. In addition, it has been demonstrated that inamrinone has a greater than additive vasodilatory effect when used in combination with NTG [76].…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 99%
“…Favorable effects of inamrinone on the IMA [76,[86][87][88] have been reported. In addition, it has been demonstrated that inamrinone has a greater than additive vasodilatory effect when used in combination with NTG [76]. It was also demonstrated that systemically administered milrinone and nitroglycerin dilate the IMA after cardiopulmonary bypass [82].…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation